Dizzy's bird watch - Inches, Alison; Mendenhall, Cheryl (New York : Simon Spotlight, 2001)
Bob the builder leaves Dizzy the cement mixer to guard a nest of eggs.
Keywords: Bob the Builder (Fictitious character) -- Juvenile fiction; Birds -- Nests -- Juvenile fiction; Trucks -- Juvenile fiction; Roads -- Maintenance and repair -- Juvenile fiction